(untitled) (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The COVID-19 pandemic had impacted teaching and learning (P&P) at schools and higher institutions. The schools closure due to the Movement Control Order (MCO) had prompted the Ministry of Education Malaysia (MOE) to prepare a Teaching and Learning at Home Manual (PdPR) as an alternative to teaching and learning in the new norms. Practical assessment in Islamic Education subjects such as servitude (Ibadah) and Islamic Jurisprudence (fikh) is a challenge in providing the understanding to the students. In addition, the attendance and commitment of students in learning sessions are the matters that need to be given attention to in observing the effectiveness of the teaching and learning. Thus, this study aims to identify the online teaching and learning methods for Islamic Education subjects in Maahad Hafiz School, Klang. This study also examines the teachers' perspectives on online teaching and learning methods (P&P) on Islamic Education subjects and analyzes its effectiveness. This descriptive study will be using both qualitative and quantitative data. Library method is used to analyze documents such as reports and circulars from the MOE. Semi-structured interviews are also used in this study on two selected teachers. The quantitative data is obtained using a questionnaire method on 12 teachers at Sekolah Maahad Hafiz, Klang. The data of this study are analyzed using frequency, percentage, and mean methods by statistical testing using Statistical Package For The Social Science (SPSS) version 22.0. The result shows that all of the teachers prefer to use the Google Meet application in their teaching and learning process as compared to other applications. The study also found that the effectiveness of online teaching & learning is high with the mean of 3.99. Nevertheless, all of the teachers prefer the face-to-face method rather than the online method. The teachers also agreed that online teaching and learning must be made as a new platform in education even though there are many challenges for the teachers in applying this method such as the accessibility of the internet, students’ awareness in the classroom and teachers’ delivery in assuring the students’ comprehension.